Advancement in molecular diagnosis of post kala-azar dermal leishmaniasis - Keerti Kaumudee Dixit; Ruchi Singh; Poonam Salotra (Wolters Kluwer Medknow Publications, 2020)
Post kala-azar dermal leishmaniasis (PKDL), a clinical sequela of visceral leishmaniasis (VL), plays a critical role in the anthroponotic transmission of VL, particularly in the Indian subcontinent (ISC). The early, accurate, and feasible diagnosis of PKDL is essential for the attainment and sustenance of VL elimination goal in ISC. PKDL poses a stumbling block for this goal, considering the heterogeneity presented with regard to time after cure of VL and onset of PKDL, chronicity, and clinical variations. In most of the endemic regions the diagnosis is based on clinical examination, previous history of VL, by ruling out other disorders, and by the response to treatment. The conventional microscopic examination involving the demonstration of Leishman-Donovan bodies (LDB) in macrophages is pathognomonic, however, the method faces constraints in terms of being invasive, less sensitive, technically demanding, and difficult to be applied in field conditions. Serological evidences are of limited use because antileishmanial antibodies remain positive for years after VL treatment. Molecular tools such as PCR, nested-PCR, Q-PCR overcome these constraints and have become increasingly popular due to their high sensitivity and specificity along with their applicability in diverse clinical samples. Molecular methods not only play a key role in early detection but also provide quantification and monitoring of treatment effectiveness. NCBI PubMed search tool was used for locating, selecting, and extracting research articles pertinent for this review article by using various related terminologies on the molecular diagnosis of leishmaniasis.